Online Disinformation and Its Implications on COVID-19 Vaccine Acceptance in Taraba State, Nigeria - Achor, Apeh Samuel (International Journal of Education, Culture, and Society, 2025)
The outbreak of the COVID-19 pandemic was accompanied by a surge of disinformation circulating on online platforms. Among the prevailing conspiracy theories were claims that the COVID-19 vaccine was hazardous and specifically designed to eradicate the Black race. This study investigates the implications of online disinformation on COVID-19 vaccine acceptance among residents of Jalingo metropolis in Taraba State, Nigeria. Adopting a qualitative research approach, data were collected through focus group discussions and in-depth interviews, which were conducted until thematic saturation was achieved. The findings reveal a widespread presence of disinformation about the COVID-19 vaccine on online platforms, particularly social media. This disinformation significantly undermined vaccine acceptance among the local population. The study concludes that online disinformation poses a serious threat to public health efforts, especially in the context of vaccine uptake. It recommends the strategic and continuous dissemination of credible information to counteract false narratives during outbreaks of novel diseases such as COVID-19.